PERLINDUNGAN HUKUM BAGI PEMEGANG SAHAM MINORITAS PADA PERSEROAN TERBATAS TERTUTUP DALAM RANGKA PENGENDALIAN PERUSAHAAN SEBAGAI UPAYA UNTUK MEWUJUDKAN KEADILAN BERDASARKAN PANCASILA - Mustaqim Mustaqim (Fakultas Hukum, 2018)
AbstractThe difference in majority shareholders with minorities is in ownership of the number of shares, often in principle, the majority shareholder causes minority shareholders in a weak position. This condition makes minority shareholders treated unfairly by majority shareholders. The GMS does not reflect legal protection for minority shareholders. This is because in every decision making in the GMS it is always based on the quorum of attendance by referring to the majority of votes present. This is detrimental to the interests of minority shareholders, because without the presence of minority shareholders the GMS is held while minority shareholders have the same rights and obligations and responsibilities to the Company. The treatment of majority shareholders against minority shareholders has not been able to guarantee minority shareholders to obtain justice based on Pancasila justice. This is because the majority shareholders in a closed limited company still have full control over the company.Keywords : Legal protection, minority shares and justice